Undergraduate students future career intention in the hotel industry: The impact of implementing the certified internship program - Ferdian, Feri; Yulastri, Asmar; Zahari, Mohd Salehuddin Mohd; Suyuthie, Hijriyantomi; Pasaribu, Pasaribu (Universitas Negeri Padang, 2025)
This scholarly investigation examines the effect of hotel hallmarks of the hotel industry, service quality of internship and internship satisfaction on undergraduate hotel management students' future career intentions in the hotel industry. A quantitative approach through a cross-sectional study with a self-reported survey questionnaire was undertaken. The sample and the unit of analysis is among hotel management students from Universitas Negeri Padang, West Sumatera, Indonesia who had undergone internships program. The study employs Partial-least Square-Structural Equation Modelling (PLS-SEM) in response to the hypotheses. The results clearly demonstrated that hallmarks of the hotel industry (less pleasant work environments, heavy job responsibilities, slow career development opportunities, and less recognition of work achievement) did not possess negative impact on hospitality interns’ students future career intentions in the hotel industry. Hotel internship service quality and internship satisfaction strongly influence hospitality interns’ students future career intentions in the hotel industry. The findings manifestly provide valuable insights and far-reaching consequences for students, hospitality institutions, industry stakeholders and policymakers.